Вавилонская гиря XVI в. до н. э. с клинописной надписью из раскопок Мецамора - Ханзадян, Э. В. (1983)
Chanzadjan, Emma - Sarkisjan, Gagik - Diakonoff, Igor, А XVI Century B.c. Babylonian Weight-Stone with a Cuneiform Inscription from the Metsamor Excavations; engl. Résumé S. 295-297; Ulam-Burariaš s. of Burna-Вurariaš.